Radiological Evaluation of the Proximal Femoral Geometric Parameters of Adult Bangladeshi Population (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: The present study is aimed to determine the value of proximal femoral parameters such as Femoral Neck Shaft Angle (FNSA) Femoral Neck Length (FNL) and Femoral Neck Width (FNW) of both sexes and also on both sides for the purpose of adequate planning, preparation and pre-operative selection of prosthetic implants and also stocking of prosthesis implants in hospitals located in developing countries like Bangladesh. Materials and methods: It was a cross sectional observational study and was conducted by Department of Anatomy, Chittagong Medical College from July 2020 to June 2021 among 200 (119 male, 81 female) normal adult Bangladeshi population of Chattogram district. Normal participants, both male and female were recruited from Radiology Department of Chittagong Medical College Hospital (CMCH) as per enrolment criteria. After taking demographic data of all participants plain pelvic X-ray A/P view were taken and reported by an expert radiologist of CMCH. Only normal radiographs were included in the study. All measurements such as FNSA, FNL and FNW of femur were taken from both sides of the X-rays. Data were analyzed by SPSS version–25. Results: In this study, mean FNSA, FNW and FNL were found larger in male than in female. The FNSA, FNW and FNL all were found higher in right side than the left and also statistically significant. Conclusion: The result of the present study provides some baseline information about proximal femoral parameters of adult Bangladeshi population which will help to design the prosthesis for hip replacement.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 9-13